2012
DOI: 10.1111/j.1399-5448.2012.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D levels are lower in Australian children and adolescents with type 1 diabetes than in children without diabetes

Abstract: Vitamin D is synthesised in the skin through the action of UVB radiation (sunlight), and 25-hydroxy vitamin D (25OHD) measured in serum as a marker of vitamin D status. Several studies, mostly conducted in high latitudes, have shown an association between type 1 diabetes mellitus (T1DM) and low serum 25OHD. We conducted a case-control study to determine whether, in a sub-tropical environment with abundant sunlight (latitude 27.5°S), children with T1DM have lower serum vitamin D than children without diabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 46 publications
7
76
1
Order By: Relevance
“…Our research is in line with previous research conducted in RSSA Malang, 90% of children with T1DM had low levels of 25(OH)D 3 [14]. The same result also obtained in various countries, such as in the United States, Switzerland, and Australia, where in patients with T1DM suffered from vitamin D deficiency and insufficiency [11,12,13].…”
Section: Subject Characteristicssupporting
confidence: 80%
See 1 more Smart Citation
“…Our research is in line with previous research conducted in RSSA Malang, 90% of children with T1DM had low levels of 25(OH)D 3 [14]. The same result also obtained in various countries, such as in the United States, Switzerland, and Australia, where in patients with T1DM suffered from vitamin D deficiency and insufficiency [11,12,13].…”
Section: Subject Characteristicssupporting
confidence: 80%
“…Research in various countries, such as in the United States, Switzerland, Australia, and Indonesia mentioned that people with T1DM suffered from vitamin D deficiency and insufficiency [11,12,13,14]. Administration vitamin D3 supplementation can prevent or reduce autoimmune damage and destruction of pancreatic β cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of association between UV30 and 25-hydroxyvitamin D was similarly reported by Greer et al [15]. In this study, it could indicate that children and adolescents with T1D may have decreased time outdoors, as the UV30 is only a measure of ambient UV light and does not necessarily represent any individual's time spent outside or amount of skin exposed to sunlight.…”
Section: Discussionmentioning
confidence: 50%
“…A study in Qatari youth with age-matched controls reported increased 25-hydroxyvitamin D deficiency/insufficiency with T1D [14]; however this population may not be generalizable to US children due to a much higher overall prevalence of vitamin D deficiency/insufficiency reported amongst the Qatari (90.6% in subjects with T1D compared to 85.3% in control subjects). In Australia, Greer et al also reported a significant difference between groups [15]. In contrast, it has been reported in Denmark that no difference was detected between children with newly diagnosed T1D and their healthy siblings [16].…”
Section: Introductionmentioning
confidence: 86%
“…These mechanisms explain how the balance resulting from calcitriol-VDR interaction finally results in a controlled activation of T-cell differentiation and effector function, allowing proper response against infections or cancer after antigen presentation, meanwhile avoiding excessive autoimmune activation [11]. This is also indirectly proven by the association found between low serum levels of vitamin D and development of autoimmune diseases, indeed known to be latitude dependent (due to the low exposure to sunlight at higher degrees of latitude) [12,13], and by the link between low serum levels of 25(OH)D and higher susceptibility to various infections [14][15][16].…”
mentioning
confidence: 96%